Biomedical Nanomaterials From design and synthesis to imaging, application and environmental impact - Stoika, Rostyslav S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book characterizes how to design and synthesize nanomaterials of an organic and mineral nature. The book also discusses the visualization of developed nanomaterials and their bio-applications, as well as describes the biomedical effects and environmental impact of nanomaterials. This is an ideal book for students studying biomedicine or the life sciences, as well as researchers and professionals in medicine, environmental protection, biotechnology, agriculture, and the food industry. More specifically, this book addresses the important nanomaterials and nanobiotechnologies that are used in those fields in biomedicine and life sciences.
1. Principal trends in nanobiotechnology -- 2. Molecular design, synthesis and properties of surface-active comb-like PEG-containing polymers and derived supramolecular structures for drug delivery -- 3. A novel water-soluble C60 fullerene-based nano-platform enhances efficiency of anticancer chemotherapy -- 4. Magnetic iron oxide particles for theranostics -- 5. Regulated Delivery and Decreased Negative Side Effects of Anticancer Drugs Complexed with Polymeric Nanocarrier -- 6. Nano- and microparticles and their role in inflammation and immune response -- 7. Basic principles of nanotoxicology -- 8. Bio-imaging, biocompatibility and functionality of polymeric nanocarriers for gene delivery -- 9. Uptake, Bio-distribution, and Mechanisms of Toxicity of Metal-Containing Nanoparticles in Aquatic Invertebrates and Vertebrates -- 10. Role of metallothionein system in response to toxic action of metal-based nanomaterials and products of their decomposition as environmental pollutants -- 11. Environmental nanoparticles: Focus on multipollutant strategy for environmental quality and health risk estimations.
Keywords: Biomedical engineering; Biomaterials; Nanotechnology; Nanoparticles; Biomedical Engineering and Bioengineering; Biomaterials; Nanotechnology; Nanoparticles; Nanostructures